Removal of basic dye from industrial wastewater by adsorption - Singh A.K.; Tiwari P.N. (My University, 2025)
For proper understanding, the process of removal of solute dye by adsorption and to reveal the manner in which this adsorption process can be adopted for removal of the solute material from the solution, the study of isotherm, kinetics and thermodynamic parameters is of paramount importance. The growth of adsorption with time is function of the initial concentration, temperature and pH of the system. The kinetics of adsorption was found to be of first order with intra-particle diffusion at the rate-controlling step. The values of different thermodynamic properties such as ΔG0, ΔH0 and ΔS0 indicate that the process is spontaneous, feasible and exothermic in nature. The adsorption process satisfies Langmuir isotherm.